Biomaterials promote in vivo generation and immunotherapy of CAR-T cells - Qin, Ya-Ting; Li, Ya-Ping; He, Xi-Wen; Wang, Xi; Li, Wen-You; Zhang, Yu-Kui (Frontiers in Immunology, 2023)
Chimeric antigen receptor-T (CAR-T) cell therapy based on functional immune cell transfer is showing a booming situation. However, complex manufacturing processes, high costs, and disappointing results in the treatment of solid tumors have limited its use. Encouragingly, it has facilitated the development of new strategies that fuse immunology, cell biology, and biomaterials to overcome these obstacles. In recent years, CAR-T engineering assisted by properly designed biomaterials has improved therapeutic efficacy and reduced side effects, providing a sustainable strategy for improving cancer immunotherapy. At the same time, the low cost and diversity of biomaterials also offer the possibility of industrial production and commercialization. Here, we summarize the role of biomaterials as gene delivery vehicles in the generation of CAR-T cells and highlight the advantages of in-situ construction in vivo. Then, we focused on how biomaterials can be combined with CAR-T cells to better enable synergistic immunotherapy in the treatment of solid tumors. Finally, we describe biomaterials' potential challenges and prospects in CAR-T therapy. This review aims to provide a detailed overview of biomaterial-based CAR-T tumor immunotherapy to help investigators reference and customize biomaterials for CAR-T therapy to improve the efficacy of immunotherapy.